Posttraumatic growth after burn in adults: An integrative literature review - Martin, L.; Byrnes, M.; McGarry, Sarah; Rea, S.; Wood, Fiona (Pergamon Press, 2017)
© 2016 Elsevier Ltd and ISBI Posttraumatic growth after burn is a relatively new area of study with only a small number of studies that have examined this phenomenon. It is important to understand the presentation of posttraumatic growth and coping in burn survivors, how it changes over time and the components which influence growth so that we can understand how to promote posttraumatic growth in burn survivors. The aim of this review was to assess these three parameters. Studies were identified through multiple databases with specific search terms to identify posttraumatic growth after burn. From the 813 articles found, 57 were identified as potentially useful, and 8 as eligible for review; three qualitative, one mixed methods, two quantitative, one discussion paper and part of a review which assessed all psychosocial outcomes. Growth presented as realising personal strength, reprioritising, spirituality, humanity, changed relationships, and compassion and altruism. Styles of coping included feelings of gratefulness and downward comparison, humour and planning. Suddenness of the event, and the severity and location of injury might affect the amount of growth experienced. Overall function, quality of life, social support and optimism, hope and new opportunities are influences on growth after burn, all of which have the potential for improvement through targeted intervention strategies. Further research is indicated in many areas related to growth, intervention and measurement.